A mechanically durable, excellent recyclable 3D hierarchical Ni3S2@Ni foam photothermal membrane - Zhongping Yao; Kailun Yu; Mengyao Pan; Hongbo Xu; Tianqi Zhao; Zhaohua Jiang (Green Energy & Environment, 2022)
Solar-driven water evaporation is considered to be a viable and very efficient technology for fresh water production. Unfortunately, the photothermal membrane has a low absorptivity, low photothermal conversion and poor recyclability, which are difficult to meet the demands of self-floating solar driven evaporators in practical applications. Herein, a hierarchical nanostructure Ni3S2 has been prepared by in-situ growing method on Ni foam (NF), which shows excellent absorptivity, outstanding recyclable and high mechanically durable properties. The photothermal membrane was composed of hierarchical nanostructure Ni3S2@NF, which exhibited excellent solar absorption (93.13%) in the wavelength range of 250 –2500 nm and sustained anti-corrosion capacity for one month. In addition, the hierarchical nanostructure Ni3S2 @NF has good hydrophilicity and strong binding force, indicating this photothermal membrane exhibits good stability and outstanding photothermal conversion efficiency. An evaporation system based on 3D Ni3S2@NF membrane exhibited excellent water evaporation ability，the highest water evaporation rate (1.53 kg m−2 h−1) and the photothermal conversion efficiency （84.7%） under 1 sun illumination. In the desalination experiment, the water evaporation rate and photothermal conversion efficiency almost keep constant over 5 cycles tests and do not decrease compared with the experiment in pure water. This result demonstrated that the Ni3S2@NF membrane has shown good corrosion resistance and outstanding recyclability. Due to the simple preparation method, low cost, outstanding recyclability and high mechanical durability in the sea water, this Ni3S2@NF membrane have great potential for long-term solar distillation applications.